DEFINITION OF THE SUBJECT AND OBJECT OF UNAUTHORIZED INTERFERENCE IN THE WORK OF INFORMATION (AUTOMATED), ELECTRONIC, INFORMATION AND COMMUNICATION SYSTEMS, ELECTRONIC COMMUNICATION NETWORKS (ARTICLES 361, 361-1 OF THE CRIMINAL CODE OF UKRAINE) - Dryzhakova, Dina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the legal status of the subject and object of unauthorized interference with the operation of information (automated), electronic, information and communication systems and electronic communication networks. Research methods: the article uses the dialectical method of cognition, general scientific and special research methods. In particular, structural-functional, deductive methods and the method of scientific forecasting. Results: the issues raised allow us to explore the problems associated with the rapid development of technology and the increasing number of interventions in the work of information (automated), electronic, information and communication systems and electronic communication networks, which leads to the need to improve legislation. Discussion: the article provides a criminal law description of the subject and object of unauthorized interference with the operation of information (automated), electronic, information and communication systems and electronic communication networks. The author concludes that to properly classify criminal offences related to unauthorised interference with the operation of information systems, it is necessary to clearly define the subject matter of these offences at the legislative level. This includes electronic, information and communication systems, and electronic networks. It is important to determine what is included in the concept of computer information. Additionally, legislators should consider that these offences involve constantly evolving and expanding objects.